Exploring Basic Problem of Arabic Speaking Skill in Foreign Language Learning - Ahmad Mubaidillah; Khoirurrijal Khoirurrijal; Husnul Fatarib; M. Kholis Amrullah; Achmad Yani (Lughatu Ad-dhat, 2023)
The main problems that arise in the process of learning speech skills and the impact of these problems on the result of the students' study and the efforts made by the Arabic linguistics in overcoming the problem of speech in Arabic at Bustan Science Islamic Intermediate School Jayasakti. This research is to identify the problems in the process of learning speech skills and the impact of problems on the outcome of students' study and the efforts made to overcome this problem. As for the form of linguistic education experienced by students at Bustan Islamic Intermediate Science School, Jayasakti has an impact on the result of students' study on understanding and implementation of speech skills, and the impact is divided into three areas, namely the cognitive and psychological impact of skills. Some efforts that can be made to overcome these problems include getting students used to speaking Arabic always, teachers try to increase students' motivation to love Arabic and try to establish a language environment.